Perilaku Inflasi 33 Propinsi Di Indonesia - Birgitta Dian Saraswati; David Kaluge (MediaTrend, 2017)
This study aims to identify the effect of food prices and the factors of demand side on the inflation rate in the 33 provinces in Indonesia. Using fixed effect panel data regression model, our result show that inflation in 33 provinces in Indonesia are caused by demand-side factors ( gross regional domestic product and government expenditure) as well as supply-side factors, namely food prices in this case the price of rice. The policy implication of this study is that monetary policy by controlling the money supply is still effective for achieving the goal of price stability. However, monetary policy alone will not be effective to achieve the inflation target. Required policy coordination among agencies or departments in order to ensure the availability of basic necessities such as rice commodities.